2010
DOI: 10.1159/000312657
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Neurological Syndromes and the Role of PET Imaging

Abstract: Paraneoplastic neurological syndromes are immune-mediated effects of cancer that involve the nervous system and are associated with various anti-neuronal antibodies. They can be associated with several cancers such as lung, gynecologic, thymic, testicular and others, but the diagnosis of cancer often becomes a challenge, since paraneoplastic neurological syndromes usually precede the cancer presentation by months or even years. Furthermore, even when the cancer develops, the tumor size remains small and usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 111 publications
(57 reference statements)
0
10
1
Order By: Relevance
“…Several studies [10][11][12] showed evidence of higher specificity and sensitivity of 18 FDG PET imaging than other conventional diagnostic tests and imaging in the diagnosis of cancer associated with PNS, but in our patient the presence of a breast carcinoma was suspected on the basis of mammography, US, CT scan and MRI while PET findings were non specific.…”
Section: Dear Sirscontrasting
confidence: 58%
“…Several studies [10][11][12] showed evidence of higher specificity and sensitivity of 18 FDG PET imaging than other conventional diagnostic tests and imaging in the diagnosis of cancer associated with PNS, but in our patient the presence of a breast carcinoma was suspected on the basis of mammography, US, CT scan and MRI while PET findings were non specific.…”
Section: Dear Sirscontrasting
confidence: 58%
“…Gultekin et al reported that 28 (64%) of 44 PLE patients had abnormal MRI findings, such as unilateral or bilateral temporal lobe abnormalities on T2-weighted images, and 5 (20%) of 25 patients had enhanced lesions (12). In addition, in most cases of PLE, 18 F-FDG PET usually shows hypermetabolism in the temporal lobes with negative findings on MRI or the presence of T2-hyperintense mesiotemporal lesions, and the 18 F-FDG PET may be correlated with disease activity (13).…”
Section: Discussionmentioning
confidence: 99%
“…The PNS are rare complications of cancer (\1 %), but they are associated with a high morbi-mortality, very often responding only to the treatment of the underlying tumor [16]. Up to 60 % of patients with PNS have highly specific onconeural antibodies and certain presentations are most frequently linked to malignancy (the so-called classical syndromes) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have reported on the usefulness of 18 F-FDG-PET in PNS, but its accuracy seems to be related to the pre-test probability [9][10][11][12][13][14][15][16][17][18][19][20]. Nevertheless, only Vaidyanathan et al [21] evaluated PET/CT in terms of pre-test clinical probability and its relation to the final detection of malignancy.…”
Section: Introductionmentioning
confidence: 99%